CanadiEM: Accessing a Virtual Community of Practice to Create a Canadian National Medical Education Institution. Issue 1 (2nd November 2018) - Ting, Daniel K.; Thoma, Brent; Luckett‐Gatopoulos, S.; Thomas, Adam; Syed, Shahbaz; Bravo, Michael; Zaver, Fareen; Purdy, Eve; Kwok, Edmund S.H.; Chan, Teresa M.
Abstract: Background: The rise of free open‐access medical education (FOAM) has led to a wide range of online resources in emergency medicine. Canadian physicians have been active contributors to FOAM. Objectives: We aimed to create a virtual community of practice that would serve as a national platform for collaboration, learning, and knowledge dissemination. Methods: CanadiEM was formed in 2016 from the merger of two Canadian websites and a podcast. Using a community‐of‐practice model, we introduced two training programs to support junior community members in becoming core editorial team members and employed asynchronous Web technologies to facilitate collaboration. We also introduced a coached peer review process and formed strategic alliances that aim to ensure a high quality of publication. Results: CanadiEM has become a portal for readers to access a broad range of FOAM content. The website has published 782 articles. Of these, 71 have undergone a coached peer review process. The website has received over 2.5 million page views from 217 countries, and the associated CRACKCast podcast has been downloaded over 750, 000 times. Conclusions: CanadiEM has succeeded in building a national multi‐interface dissemination network that fosters collaboration and knowledge sharing in emergency medicine while fostering junior digital scholars. The construction of a community of practice has been facilitated by quality assurance, training programs, and the use of asynchronous Web technologies. Ongoing challenges in sustainability include a volunteer workforce with high turnover.